Neuroprotective Effect of Mixed Mushroom Mycelia Extract on Neurotoxicity and Neuroinflammation via Regulation of ROS-Induced Oxidative Stress in PC12 and BV2 Cells - Sang-Seop Lee; Da-Hyun Ko; Ga-Young Lee; So-Yeon Kim; Seung-Yun Han; Jong-Yea Park; MiNa Park; Hyun-Min Kim; Ya-El Kim; Yung-Choon Yoo (Cells, 2025)
In this study, we investigated the potential of a three-mushroom complex extract (GMK) to inhibit neuronal cell death induced by the activation of AMPA and NMDA receptors following glutamate treatment in NGF-differentiated PC12 neuronal cells. GMK significantly mitigated glutamate-induced excitotoxic neuronal apoptosis by reducing the elevated expression of BAX, a critical regulator of apoptosis, and restoring BCL2 levels. These neuroprotective effects were associated with redox regulation, as evidenced by the upregulation of SOD, CAT, and GSH levels, and the downregulation of MDA levels. Mechanistic studies further revealed that GMK effectively scavenged ROS by downregulating NOX1, NOX2, and NOX4, while upregulating NRF1, P62, NRF2, HO1, and NQO1. Additionally, in the same model, GMK treatment increased acetylcholine, choline acetyltransferase, and GABA levels while reducing acetylcholinesterase activity. These effects were also attributed to the regulation of redox balance. Furthermore, we investigated the antioxidant and anti-inflammatory mechanisms of GMK in LPS-stimulated BV2 microglia. GMK inhibited the activation of IκB and MAPK pathways, positively regulated the BCL2/BAX ratio, suppressed TXNIP activity, and upregulated NQO1 and NOX1. In conclusion, GMK improved neuronal excitotoxicity and microglial inflammation through the positive modulation of the redox regulatory system, demonstrating its potential as a natural resource for pharmaceutical applications and functional health foods.